Impact of Globalization of Small Scale Industries: Analysing the Growth of SSIs & The Policy Reforms - Deene, Shivakumar; Madari, D. M (Journal of Commerce and Trade, 2007)
“Small is beautiful”. Indeed, the Gandhi was also in famous of small scale and in particular village industries. The environment school has pressed the need for small is indispensable is a sustained economic development. At present, the small scale industries are defined as undertaking with investment in plant and machinery, not more than Rs.1 crore, and tiny units as those with an investment of not more than Rs.25 lacks. Globalisation witnessed the intended benefits. Not only that, the entry of multinationals in ordinary consumer goods like ice cream, Agarbatti manufacturing, food processing, mineral water etc., is also adversely affecting the SSI sector since these were the traditional areas of this sector. This way, Government must secure the SSI Sector as workforce engagement, job opportunities and less investment assume as special significance.